Advanced MDCT assessment of abdominal aortic wall integrity and morphometry in the Saudi cohort: A single-centre cross-sectional study - Mohammad Ahmad Mostafa Alloush; Mazin Babikir Hassib; Husain Alturkistani; Rafat S. Mohtasib; Rashed Ali Alhamed; Reham Mukhlid Almutairi; Mohammed J. Alsaadi (PLoS ONE, 2025)
Background Accurate reference values for abdominal aortic dimensions and wall thickness are crucial for the early detection and management of vascular diseases, particularly abdominal aortic aneurysms (AAAs). However, there is a lack of population-specific normative data for the Saudi population. Methods A cross-sectional study was conducted on 347 adults [111 males, 236 females] aged 20–80 at King Fahad Medical City. Multidetector computed tomography (MDCT) was utilised to measure the abdominal aortic lumen area, diameter, and wall thickness at three standard anatomical levels. Pixel-based segmentation and image analysis using MATLAB allowed for precise quantification of wall thickness. Multiple linear regression was employed to assess associations with age, gender, and BMI. Results The average diameter of the aorta was 1.87 cm, the average wall thickness was 1.6 mm, and the average lumen area was 3.01 cm². Males generally had thicker aortic walls and larger dimensions than females, particularly in younger age groups. However, these gender differences became less pronounced with older age and increased BMI. A higher BMI was strongly linked to thicker aortic walls (p < 0.001) but was also associated with a reduced lumen area (p < 0.001). Importantly, aortic diameter did not significantly influence wall thickness. Conclusion This study provides essential normative data for abdominal aortic measurements in the Saudi population, highlighting age and BMI as significant influencers of aortic morphology. The results support the adoption of population-specific diagnostic criteria and demonstrate the utility of advanced MDCT-based measurement techniques in vascular assessment.